Measures Used to Sustain Hospitality and Tourism Industry During the Covid-19 Pandemic in Selected Establishments in the Copperbelt Province in Zambia - Selina Banda; Florence Phiri; Margaret Pansho; Marian Mtonga; Jack Kaale (Jurnal Pariwisata Nusantara (JUWITA), 2022)
Purpose: This study explored sustainability measures used in the hospitality and tourism industry and determined their effectiveness during the COVID-19 pandemic in selected towns in the Copperbelt Province. Methods: With an interpretative stance, a phenomenology qualitative research was conducted among 15 participants who were purposively selected. Data were collected using interviews and analyzed thematically. Result: We found out that measures are used to sustain the hospitality and tourism industry.  The majority of the participants effectively used the measures to sustain their establishments while a few did not. There is a need for preparedness in the industry in case of any adverse changes occurring in the environment    Contribution:  This research contributes a qualitative interpretation of how the hospitality and tourism industry sustained itself during the COVID-19 era. It provides a basis for informed decision-making in sustaining the industry amidst uncertainties Originality: The study used a qualitative perspective to understand phenomena regarding the sustainability of tourism during the pandemic which was novel in Kitwe District.